2013
DOI: 10.1017/s1041610213000744
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence survey of drugs useful in prevention of dementia of Alzheimer's type among Indian patients

Abstract: Compliance to drugs that have potential or real ability to slow down cognitive decline is low in elderly people with DAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 18 publications
2
23
1
Order By: Relevance
“…[13][14][15][16] Previous reports have demonstrated that ignorance about the importance of treatment, the lack of awareness, and previous occurrence of medication nonadherence, all contributed to poor medication adherence. 17,18 The higher rate of discontinuation in our study shows similar reasons. Our survey indicates that misunderstandings about the efficacy of antidementia treatment is one of common reasons that patients withdraw from treatment, including lack of efficacy, treatment refusal and lack of awareness.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…[13][14][15][16] Previous reports have demonstrated that ignorance about the importance of treatment, the lack of awareness, and previous occurrence of medication nonadherence, all contributed to poor medication adherence. 17,18 The higher rate of discontinuation in our study shows similar reasons. Our survey indicates that misunderstandings about the efficacy of antidementia treatment is one of common reasons that patients withdraw from treatment, including lack of efficacy, treatment refusal and lack of awareness.…”
Section: Discussionsupporting
confidence: 78%
“…Patients with a high level of education are more likely to adhere to medication regimens Previously, Dhikav et al found that illiteracy and lower education levels were primary factors contributing to poor drug adherence. 17 In another study, having more years of formal education decreased the risk of treatment discontinuation in patients with dementia. 19 In our study, patients with higher education levels adhered to their drug treatments longer than patients with lower education levels.…”
Section: Discussionmentioning
confidence: 96%
“…In this predominantly elderly group with impaired cognition, compliance is often poor and the potential for misdosage high. Forty-one per cent of patients with AD on cardiovascular drugs were not taking their drugs regularly [52]. Furthermore, although widely used, drugs to treat VRF are not uncommonly associated with side effects, particularly in the elderly population most affected by AD, which can reduce quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore likely that, for the current study, the cognitively healthier persons in the nutritionally frail population were selected, and this can be seen as a certain selection bias. Consequently, the results should not be generalized to cognitively impaired persons, who most likely face issues relating to unintentional non-compliance, for example by simply forgetting to consume their medications and ONS prescriptions (Dhikav, Singh, & Anand, 2013). Their compliance might therefore rely less on person factors and values, and more on attributes such as a good taste, small volume, or facilitation of ONS by their caregiver.…”
Section: Discussionmentioning
confidence: 99%